Building Basic Life Skills in Students of SMAN 2 Padang Panjang - Dwi Puspasari; Nelia Afriyeni; Siska Oktari; Liliyana Sari; Rani Armalita; Tri Rahayuningsih; Helyuza Ridwan; Armen Danur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Students are one group of individuals who are in adolescent development. Adolescence is the stage of human development between childhood and adulthood. Growth and development are also felt in adolescence, including cognitive, personality, social, and physical development. Adolescence is the next generation of the nation's struggle and has a vital role in the nation's survival. Thus, various skills are needed in adolescents to face the development and challenges that lie ahead. One of the things that can be done is to provide debriefing related to essential life skills. Debriefing is done through training activities to increase students' knowledge of essential life skills. The participants of this activity were 27 students of SMAN 2 Padang Panjang. Training activities are packaged through applicative, interactive, and simple games that illustrate essential life skills—measurement of knowledge in students using an open-ended questionnaire that refers to essential life skills. After receiving training, we observed an increase in grades/scores in students, which was measured through a pre- and post-training assessment of their understanding and application of the essential life skills.